Storm Warning: The 39 Clues #9 - Park, Linda Sue (New York : Scholastic Inc., 2010)
Throughout the hunt for the 39 Clues, Amy and Dan have encountered some of the darkest aspects of history . . . and had to deal with the role their family played. But are they ready for the truth? In this thrilling ninth installment, Amy and Dan hit the high seas as they follow the trail of some infamous ancestors to track down a long lost treasure. However, the real prize isnt hidden in a chest. It's the discovery of the Madrigals' most dangerous secret and, even more shockingly, the true identity of the mysterious man in black.
Keywords: Cahill, Amy (Fictitious character) -- Juvenile fiction; Treasure troves -- Juvenile fiction; Cahill, Dan (Fictitious character) -- Juvenile fiction; Family secrets -- Juvenile fiction